Pemberdayaan Masyarakat : Edukasi KEK Remaja Putri di MTS PKP Al-Hidayah Kota Jambi - Liya Putri Rahmaniya; Siti Fati Hatussaadah; Iin Indrawati (Universitas Baiturrahim, 2026)
Adolescents experience various changes such as relatively rapid growth and development in physical, mental, emotional, and even social. Adolescents will be prone to experiencing nutritional problems if the growth and development process is not accompanied by balanced consumption of nutrients. One of the nutritional problems that often occurs in adolescent girls, is chronic energy deficiency (CED). Lack of nutritional knowledge is one of the factors that can affect the onset of CED in adolescents. CED can have a negative impact on adolescents and the next generation of life. The purpose of this activity was to increase the knowledge of adolescent girls about the nutritional status of adolescents related to CED. Community service activity in the form of providing education was carried out at MTS PKP Al-Hidayah, Jambi City from September 2025 to February 2026. The participants who attended were 21 students in grades VII and VIII. Educational activities began with a pre-test, then the delivery of educational materials using leaflets and projectors, followed by an open discussion with the participants, and ended with a post-tests. There was an increase in the knowledge value of young women as seen from the average pre-test score of 29.5 to 86.7 in the average score of the post-test. It can be concluded that there is an increase in the knowledge of adolescent nutrition status related to CED after being educated by the service team using the media that has been prepared.